Ethnic conflict : a global perspective - Wolff, Stefan, 1969- (New York, NY : Oxford University Press, 2006)
The first accessible and comprehensive introduction to the origins, dynamics, and management of ethnic conflicts. Covers a broad range of ethnic conflicts in different parts of the world, highlighting both their similarities and their differences. Shows the links between ethnic conflict and other security challenges such as terrorism and organized crime. Incorporates eye-witness testimonies from Human Rights organizations and illuminates the tragic human dimension of ethnic conflict.
Introduction: Ethnopolitics: Conflict versus cooperation -- 1: The human dimension: Facts, figures, and stories of ethnic conflict -- 2: Ethnicity and nationalism -- 3: What causes ethnic conflicts -- 4: Who fights in ethnic conflicts and how -- 5: Managing and settling ethnic conflicts -- 6: Post-conflict reconstruction -- 7: The future of ethnic conflict: Possibilities and probabilities.
Title from resource description page (viewed March 8, 2016).
Includes bibliographical references and index.
In English.
Keywords: Ethnic conflict; Ethnic relations -- Political aspects